Maintenance standard for stadium (National Stadium, Shah Alam Stadium, Darul Aman Stadium) / Mohammad Rahmat Othman - Othman, Mohammad Rahmat (2007)
Stadium has been developed for both its function and appearance. From gladiator fight in Rome, its has changed its function to sport event. Nowadays, stadiums are used for many events like outdoor sport, concert and exhibition. Stadium appearances also get into their revolution in architectural aspect. In Malaysia, most of the stadiums have the experience of bad condition either its building or pitch. The building seems to be dilapidated because of lack in use and care. This research comprises of 6 chapters. This research intends to identify the maintenance standard of stadiums. Maintenance standard is established from the policies that have been developed by management principle. A clear policy must be established to guide the maintenance efforts according to the standard. Case studies on three numbers of stadiums, two are in Selangor and one in Kedah were undertaken in the study to highlight the background of maintenance. All collected information is documented in Chapter 3. Comparative and statistical analyses of the case study are based on the questionnaire. Questionnaire is distributed to public (user) to get their opinion on the condition of stadium. All the analysis result is documented in Chapter 5.